2013
DOI: 10.14233/ajchem.2013.15308
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Free Radical Scavenging Activities of Curcumin

Abstract: Oxidative stress is an imbalance between free radicals and antioxidant systems to cause chronic diseases such as cancer, Alzheimer's and Parkinson's 1. Reactive oxygen species (ROS) and free radicals, such as hydroxyl radicals and hydrogen peroxide are produced in the human body during normal metabolic pathways and exposure to exogenous stress such as ionizing radiation and air pollutions can induce adverse effects on the normal physiological activity of cells. The body's system is equipped with antioxidant de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 3 publications
4
20
0
Order By: Relevance
“…The imbalance between free radicals and the body’s defense system against oxidative stress can cause various chronic diseases [ 23 ]. An excessive production of reactive oxygen species (ROS) can induce oxidative stress and damage essential biomolecules, while antioxidants, including antioxidant enzymes and antioxidant compounds, can protect the human body from free radicals and ROS effects, attenuating the progress of many chronic diseases [ 24 ].…”
Section: Bioactivity Of Curcuminmentioning
confidence: 99%
“…The imbalance between free radicals and the body’s defense system against oxidative stress can cause various chronic diseases [ 23 ]. An excessive production of reactive oxygen species (ROS) can induce oxidative stress and damage essential biomolecules, while antioxidants, including antioxidant enzymes and antioxidant compounds, can protect the human body from free radicals and ROS effects, attenuating the progress of many chronic diseases [ 24 ].…”
Section: Bioactivity Of Curcuminmentioning
confidence: 99%
“…Turmeric is mainly consumed as spice in India and Asia and also used in traditional medicine since ancient times.The unique structure of curcumin with its 1,3-diketo sub-structure, existing mainly in the enolic form in solution and exclusively in the solid state has created a pharmacological conundrum in that it interacts with diverse pharmacological targets without palpable toxicity even at fairly high doses. Pharmacological studies over the last few decades on curcumin have revealed its therapeutic potential as anti-cancer [ 1 ], anti-oxidant [ 2 ], anti-inflammatory [ 3 ], and antimicrobial [ 4 ] agents, and curcumin also possesses anti-arthritic [ 5 ], anti-diabetic [ 6 ], hepatoprotective [ 7 ], neuroprotectant [ 8 ] and antidepressant [ 9 ] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite its low concentration in plasma, curcumin still exhibits its biological activity even though no systematic study exists on the detection of curcumin in target tissues. Numerous studies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] have been carried out on curcumin in last few decades to understand its mechanism of action; however, the low bioavailability and retention of bioactivity of curcumin still remain unexplained conundrums. Hence, to understand the mechanism of action of curcumin more precisely, it is essential to study the biological activities/functions of its metabolites too.…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activity (radical scavenging activity %) was measured using DPPH (1,1-diphenyl-2-picrylhydrazyl) [22]. In brief, 1.5 mL of the tested materials at concentrations of 1.25, 2.5 and 5 mg/mL was mixed with 1.5 mL of 0.1 mM DPPH in ethanol.…”
Section: Antioxidant Activitymentioning
confidence: 99%